Words, beliefs, and related rites to the muqui, the goblin of the mines - Carrasco Ligarda, Rosa (2016)
It presents a selection of terms related to the muqui (the goblin of the mines) that are employed in the mining regions where drifts and tunnels are to get to the veins. Furthermore, the physical and psychological description, and nicknames that are attributed to the goblin. Besides, words related with rites and offerings are analyzed. Finally, terms employed to refer to the people responsible of performing ceremonies in rituals or implementing some related activities.